A magnetic coupling thrust stand for microthrust measurements. (17th November 2015) - Wright, W P; Ferrer, P
Abstract: A direct thrust measurement system that is based on a horizontal lever and utilizes a novel magnetic coupling mechanism to measure thrust has been developed. The system is capable of measuring thrusts as low as 10's of μ N. While zero drift is observed in the balance, tests have shown that they do not have an appreciable effect on thrust measurements. The thrust stand's sensitivity can be adjusted by shifting the position of the coupling magnet inside the stand's thrust support member, which allows flexibility for testing both higher and lower powered thrusters. The thrust stand has been modeled theoretically and the predicted results from the model are compared with experimentally measured data. The system was tested using a simple cold gas thruster and provided credible results that can be compared with other systems studied in the literature. Advantages include that the thrust stand is very cheap and easy to construct and further, the calibration process takes no longer than half an hour, facilitating rapid turnaround times while still retaining accuracy. Repeatability tests have shown that the balance gives consistent results.